Temperaturen des Begehrens. Sinnliche Präsenz und kulturelle Repräsentationen - Szczepaniak, Monika; Drynda, Joanna (Studia Germanica Posnaniensia, 2015)
The aim of the article is to present the interdisciplinary theoretical framework for the analysis of the constellation of temperature and desire as well as its representations in literature and culture, which have not been the subject of a broad reflection in the area of literary and cultural studies so far. The question therefore is: What is the role of the literary, iconographic and media discourses of temperature in the processes of the creating and transformations of emotional cultures, social phenomena, political condi-tions, and last but not least in the critical reflection of these processes.